Rational and reliable diagnosis of periprosthetic hip and knee joint infection using two nuclear-medicine methods: 99mTc-ciprofloxacin and 99mTc-MDP scintigraphy - Pucar, Dragan; Janković, Zoran; Starčević, Srdjan (Vojnosanitetski pregled, 2021)
Background/Aim. There is a constant and dramatic increase in hip and knee prosthetic implantations worldwide. However, a decrease in the percentage of failed (infected) prosthetic implantations is not significant (0.5% up to 2%). The real challenge is whether prosthetic joint loosening was caused by aseptic inflammation or by infection. The aim of the present study was to attempt to distinguish sterile inflammation from infection in patients with a painful hip or knee prosthetic joint. Another objective was to determine the accuracy of cumulative bone scintigraphy with methylenediphosphonate (MDP) and ciprofloxacin in diagnosis of periprosthetic joint infection (PJI). Methods. Three-phase bone scintigraphy with 99mTc-MDP and 99mTc-ciprofloxacin was used. The patient selection criterion for this study was a suspicion of PJI followed by painful and limited movement of the prosthetic joint, accompanied by elevated unspecific inflammatory factors. Forty five patients with 39 implanted hips and 24 knee prostheses were included and evaluated. All prosthetic joints were examined (although some of them were asymptomatic) and underwent plain radiography. An average time span between the two nuclear medicine imaging procedures was 3–5 days. Three-phase 99mTc-MDP bone scintigraphy was performed first. Scintigraphy with 99mTc-ciprofloxacin was necessarily involved calculation of the accumulation index. The obtained results were confirmed by microbiological findings as a gold standard. Statistical analysis of the results was performed using SPSS version 20 software (descriptive statistics, χ2-test). Sensitivity, specificity, and predictive values were also calculated. Results. Microbiologically confirmed PJI was found in 16 out of 39 hip prostheses. Positive scintigraphy was obtained in 15 out of 39 prosthetic hip joints. PJI was found using scintigraphy of the knee, and microbiologically confirmed in all 13 out of 24 suspected joints. Estimated sensitivity/specificity of 99mTc-MDP bone scintigraphy alone (for both joints) was 90%/69%, for 99mTc-ciprofloxacin scintigraphy it was 93%/97%, and for cumulative results it was 96.5%/97%. Conclusion. Cumulative 99mTc-MDP scintigraphy with 99mTc-ciprofloxacin scintigraphy increases the ability of differentiation between aseptic loosening and PJI, with high accuracy of 97%.